THERAPEUTIC MANAGEMENT OF AUTISM SPECTRUM DISORDER (ASD) IN CHILDREN: EARLY INTERVENTION PROTOCOLS AND A MULTIDISCIPLINARY TEAM - Decker, Gabriela; Baratto, César Meneghetti; Alves, Nicoli Viana; Oliveira, Paula Guimarães; Nunes, Miguel Carlos da Silva; Lima, Rachel Cassiano de Sousa; da Silva, Ana Paula Pio Alves; Costa, Silvia Helena Silveira Thomé; Becker, Claudia Aparecida; Toledo, Rodolfo Ricardo; Mendonça, Kauan Talles Barros; Queiroz, Évely da Silva; et al. (Seven Editora, 2026)
Autism Spectrum Disorder (ASD) is a neurodevelopmental condition characterized by impairments in social communication and restricted and repetitive patterns of behavior, presenting a multifactorial etiology involving genetic, neurological, and environmental factors. Given the increasing prevalence of the disorder and the complexity of its clinical management, this study aimed to analyze current guidelines related to the therapeutic management of ASD in children, with an emphasis on early intervention protocols and the role of the multidisciplinary team. This is a narrative literature review conducted using searches in the PubMed database, using the descriptors "Autism Spectrum Disorder", "Children", "Diagnosis", and "Treatment", combined with Boolean operators. Articles published in the last five years, available in full in Portuguese or English, and related to diagnosis and intervention strategies were included. The results indicate that early identification of the disorder and the initiation of interventions during the first years of life favor better outcomes in child development, especially in social, communicative, and adaptive skills. Evidence-based therapeutic approaches, such as Applied Behavior Analysis, the Denver Model of Early Intervention, and alternative communication systems, demonstrate positive results when applied in an integrated manner. It is concluded that the management of ASD in childhood should be individualized, evidence-based, and conducted by a multidisciplinary team, also considering the diagnosis and treatment of associated comorbidities, in order to promote greater autonomy and quality of life.